2017
DOI: 10.1016/j.addr.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

D-amino acid-containing supramolecular nanofibers for potential cancer therapeutics

Abstract: Nanostructures formed by peptides that self-assemble in water through non-covalent interactions have attracted considerable attention because peptides possess several unique advantages, such as modular design and easiness of synthesis, convenient modification with known functional motifs, good biocompatibility, low immunogenicity and toxicity, inherent biodegradability, and fast responses to a wide range of external stimuli. After about two decades of development, peptide-based supramolecular nanostructures ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 152 publications
0
60
0
Order By: Relevance
“…The remarkable chemical complementarity and structural compatibility of the self-assembled D- and L- amino acids make them beneficial materials and structures in medical applications. A recent review based on D-amino acids and their applications in cancer therapy can be found [27,97,98]. …”
Section: Peptide-peptide Interaction Driven Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…The remarkable chemical complementarity and structural compatibility of the self-assembled D- and L- amino acids make them beneficial materials and structures in medical applications. A recent review based on D-amino acids and their applications in cancer therapy can be found [27,97,98]. …”
Section: Peptide-peptide Interaction Driven Self-assemblymentioning
confidence: 99%
“…Furthermore, the peptide sequence can be designed for disease-specific enzymatic activity to control self-assembly [27] or disassembly [28], allowing for active targeting of various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent unbiased biological tests not only confirmed the desired function of EISA but also highlighted their emerging biological activities to control cell fate via induction of apoptosis, necroptosis, immune responses, and so on . In addition, small‐molecule‐based EISA shows good biocompatibility, easy clearance, and low immunogenicity and toxicity …”
Section: Introductionmentioning
confidence: 86%
“…Given that this tripeptide is capable of forming a hydrogel with mild antimicrobial activity and a lack of cytotoxicity in vitro [ 26 ], this new system could be valuable for the development of wound healing applications [ 28 ], whereby luminescence could be advantageous to visually track the presence of the hydrogel and the ability of its components to penetrate through the derma [ 29 ]. In addition, peptide hydrogels based on the Phe-Phe motif [ 30 31 ] and bearing unnatural D-amino acids [ 32 33 ] are attractive biomaterials that may display higher durability relative to traditional peptide counterparts, in addition to better biocompatibility and the possibility to incorporate bioactive motifs relative to non-peptide hydrogels. Therefore, in the long term, a supramolecular hydrogel composed of a peptide and luminescent nanodots could be valuable for tissue regeneration based on a bioactive scaffold that can be also visualized in vivo by fluorescence microscopy.…”
Section: Introductionmentioning
confidence: 99%